Depressive Symptoms and SES among the Mid-Aged and Elderly in China: Evidence from the China Health and Retirement Longitudinal Study National Baseline - Lei, Xiaoyan (Soc Sci Med, 2014)
We examine the prevalence of depressive symptoms among the mid-aged and elderly in China and examine relationships between depression and current SES factors such as gender, age, education and income (per capita expenditures). In addition, we explore associations of depressive symptoms with measures of early childhood health, recent family deaths and current chronic health conditions. We use data from the China Health and Retirement Longitudinal Study (CHARLS) national baseline, fielded in 2011/12, which contains the ten question version of the Center for Epidemiologic Studies-Depression scale (CES-D) for 17,343 respondents aged 45 and older. We fill a major gap by using the CHARLS data to explore the general patterns of depression and risk factors among the Chinese elderly nationwide, which has never been possible before. We find that depressive symptoms are significantly associated with own education and per capita expenditure, and the associations are robust to the inclusion of highly disaggregated community fixed effects and to the addition of several other risk factors. Factors such as good general health during childhood are negatively associated with later depression. There exist strong gender differences, with females having higher depression scores. Being a recent widow or widower is associated with more depressive symptoms, as is having a series of chronic health problems, notably having moderate or severe pain, disability or problems with measures of physical functioning. Adding the chronic health problems to the specification greatly reduces the SES associations with depressive symptoms, suggesting that part of the pathways behind these associations are through these chronic health factors.